Fast Fashion for 2030: Using the Pattern of the Sustainable Development Goals (SDGs) to Cut a More Gender-Just Fashion Sector. Issue 1 (22nd February 2022) - Vijeyarasa, Ramona; Liu, Mark
Abstract: The 2013 collapse of the Rana Plaza in Bangladesh brought global visibility to the human rights abuses experienced by women workers in the garment sector. As the spotlight on this incident dims, the need to hold the fashion sector accountable remains. In this article, we suggest that greater accountability could be achieved through the application of a human rights-informed understanding of the Sustainable Development Goals (SDGs) to promote gender justice in the sector. By drawing on international women's rights law and sustainable fashion, we demonstrate how sustainability and gender justice are intimately connected, and illustrate what role the SDGs can play in promoting sustainable outcomes that are gender-just. The article unpacks concepts such as sustainability, the circular economy, social responsibility, and ethical fashion, and places the experiences of women workers within this context. Its principal contribution is a set of six requirements to ensure a gender perspective to the fashion industry's role in implementing the SDGs.